Prevalence of prognostic factors for cancer of the uterine cervix after radical hysterectomy - Tavares, Marília Buenos Aires Cabral (2009)
CONTEXT AND OBJECTIVE: Cancer of the uterine cervix is still very common in Brazil. It is important to evaluate factors that influence its prognosis. The aim here was to analyze the prevalence of prognostic anatomoclinical factors among patients with carcinoma of the uterine cervix undergoing radical hysterectomy. DESIGN AND SETTING: Cross-sectional study on 301 patients with invasive carcinoma of the uterine cervix who underwent Level III Piver-Rutledge hysterectomy surgery at São Marcos Hospital. METHODS: The following variables were analyzed: age, histological type, degree of differentiation, invasion of lymphatic, vascular and perineural space, lymph node metastasis, distance to nearest margin, tumor invasion depth, vaginal cuff size, largest diameter of the tumor, presence of necrosis and surgical margin involvement. Descriptive statistics, multiple regression analysis, Kaplan-Meier survival curves and the log-rank test were performed. A significance level of 5% was used. RESULTS: The mean age was 48.27 years. The following were not important for the prognosis, in relation to survival analysis: degree of differentiation and tumor invasion depth; presence of lymphatic, blood and perineural invasions; distance to nearest margin; and vaginal cuff size. Tumor size (P < 0.036), presence of lymph node metastasis (P < 0.0004), necrosis (P < 0.05) and surgical margin involvement (P < 0.0015) presented impacts on survival. The overall survival with 98 months of follow-up was 88.35%. CONCLUSION: The most prevalent prognostic factors were the presence of lymph node metastasis, tumor size and surgical margin involvement.